Numerical Computations of Entropy Generation and MHD Ferrofluid Filled in a Closed Wavy Configuration: Finite Element Based Study - Mahmood, Rashid; Khan, Y.; Rahman, Nusrat; Majeed, Afraz Hussain; Alameer, A.; Faraz, N. (Frontiers in Physics, 2022)
In this paper, the thermal flow effects of inclined Magnetohydrodynamics (MHD) ferrofluid filled in a wavy cavity are studied by adopting the Finite Element Method (FEM). The vertical walls are considered cold whereas, the bottom wavy surface is considered heated and the top wavy surface is insulated. Effect of the pertinent parameters, like Ra=10^5, volume fraction (0.00≤ϕ≤0.06), inclination angle (0^∘≤γ≤90^∘ ) and Amplitude of the wavy surface (0.02≤AR≤0.08) is investigated. Computational results are addressed as streamlines out, isotherms, and proper graphs for substantial amounts of interest. Increasing Hartmann number (Ha) leads to an increase in Bejan number (Be) while, opposite behavior can be observed in the case of viscous, magnetic, and thermal irreversibility i.e., curves are decreased by increasing the Ha. Under the influence of an inclined magnetic field, the mathematical structuring of the problem is manifested by continuity, momentum, and energy equations. These equations are solved by using the FEM computation. The graphs of velocity and isotherm are compared to the relevant parameters. To predict the flow characteristics at different locations, cross-sectional lines representing the velocity field in the horizontal and vertical directions are also drawn. Magnetization's impact on flow control, heat transfer, and various irreversibilities are also discussed.